Summer Computer Simulation Conference (SCSC) 2017
DOI: 10.22360/summersim.2017.scsc.039
|View full text |Cite
|
Sign up to set email alerts
|

A Review Of The Use Of Business Simulation To Enhance Students" Employability (WIP)

Abstract: This paper investigates the potential use of business simulation games in enhancing employability skills of undergraduate business students in UK higher education institutions. It identifies the meaning of employability to different stakeholders in order to generate a list of skills that are considered important to various stakeholders as employers, government and academics. The benefits and learning outcomes as well as perceived limitations of business simulation games are then defined. Employability skills t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Often, lecturers will leave learning, and the process is carried out by students themselves or their groups. (Asiri et al, 2017), in their study, found that students who have experience doing business simulations are more easily accepted to work. Given the importance of the learning process that pays attention to the development of times and technology and provides practical world experience, this study aims to analyze whether the MonsoonSIM platform used by the Atma Jaya FEB Management Study Program has an impact on students' understanding of the business learning process.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Often, lecturers will leave learning, and the process is carried out by students themselves or their groups. (Asiri et al, 2017), in their study, found that students who have experience doing business simulations are more easily accepted to work. Given the importance of the learning process that pays attention to the development of times and technology and provides practical world experience, this study aims to analyze whether the MonsoonSIM platform used by the Atma Jaya FEB Management Study Program has an impact on students' understanding of the business learning process.…”
Section: Introductionmentioning
confidence: 92%
“…(Chai, 2018) The use of business simulations also supports student careers if they later choose to work in a company. According to (Asiri et al, 2017), students who study at universities with business simulation courses are found to be easier to be accepted into a company than those without business simulation experience. Of course, this is advantageous for a university if it has business simulation courses in its curriculum.…”
Section: Introductionmentioning
confidence: 99%